Septic Arthritis of the Native Ankle. Issue 3 (March 2019) - Movassaghi, Kamran; Wakefield, Connor; Bohl, Daniel D.; Lee, Simon; Lin, Johnny; Holmes, George B.; Hamid, Kamran S.
Abstract : Septic arthritis of the ankle is a serious condition that requires immediate recognition and treatment. Delay may result in permanent destruction of the cartilage and the joint, and the infection may spread to nearby tissues or cause sepsis. Staphylococcus aureus is the most common causative organism of septic arthritis of the ankle. Septic arthritis of the ankle typically presents as a tender, warm, and erythematous ankle joint with painful and limited range of motion. Serum and joint fluid analysis as well as culture and Gram staining should aid in the diagnosis. Treatment typically includes surgical drainage and antibiotic therapy.